A Survey on Communicative Problems Between Elders With Alzheimer Disease and Their Family Care Givers - Marziye Khatooni; Sima Zohari (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: This descriptive study was conducted to determine the communicative Abstract problem between elders with Alzheimer disease and there caregivers. Methods & Materials: 100 main caregivers were selected by census. data was obtained by a questionnaire with a good validity and reliability. Its reliability was measured by internal consistency (de=0.96) and test-retest (d=0.96) methods. Data was analyzed by spss soft ware. Results: Findings showed that most caregivers (74%) expressed communicative problem with patient in high level, 17% in medium level and 9% in lowlevel. Significant correlation exist between age and sex of caregivers and amount of communicative problem with patient. Higher age was associated with increasing problems and female caregivers showed higher level of that problem. Also significant correlation exist between severity of patient disease and amount of communicative problem as with increases in disease severity, communicative problem increases. Conclusion: Effective communication is an important factor in gratifying physical and psychological needs. Besides, The results of present study indicate the seriousness of communication problems between the caregivers and patients. So, training the caregivers is necessary to enable them communicated effectively. This will also help them reduce their level of burden and fatigue .